Vitamin B2 overproduction in Lactiplantibacillus plantarum: new insights in the FMN-dependent regulatory activity of the rib operon riboswitch - Angela Scauro; José Ángel Ruiz-Masó; Annel M. Hernández-Alcántara; Francisca Álvarez-Juárez; Nicola De Simone; Lidia Rodrigo; Rosa Aznar; Pasquale Russo; Giuseppe Spano; Gloria del Solar (Food Bioscience, 2026)

Database development and LIBS calibration for the LIBS-Raman Sensor for planetary exploration - E.R. Sawyers; G. Lopez-Reyes; A. Barlow; M. Veneranda; E.A. Lymer; E.A. Cloutis; J. Manrique; B. Barrios; S. Julve; J. Freemantle; M. Aznar; M.G. Daly; et al. (Icarus, 2025)

Probiotic Characteristics of Lactiplantibacillus plantarum CECT 9435 and Its Survival and Competitive Properties Under Simulated Conditions of the Child Gut Microbiota - Teresa Requena; M. Carmen Martínez-Cuesta; Rosa Aznar; M. Luz Mohedano; Paloma López; Patricia Ruas-Madiedo (Probiotics and Antimicrobial Proteins, 2025)
Probiotics are valuable microorganisms effective in reducing malnutrition-related infections in children. In this work, a collection of lactobacilli strains representative of traditional Andean fermented beverages was in vitro screened for their capability to survive the gastrointestinal transit, to adhere to the intestinal epithelium and to compete under simulated conditions of the child gut microbiota. The results allowed the selection of the riboflavin overproducing strain Lactiplantibacillus plantarum CECT 9435 based on its good rate of survival under in vitro gastrointestinal conditions when included in a food matrix representing the fortified food supplement Incaparina. The strain also showed good adhesion to HT29 cells producing mucus and outstanding performance in E. coli competition for the adhesion to this epithelial cell line. L. plantarum CECT 9435 gut performance was also evaluated in the child intestinal microbiota simulated in a dynamic gut model (BFBL simulator). The viability of the probiotic candidate in the gut conditions was high during the 7-day intervention period, reaching over 1 × 10 7 counts in each of the reactors simulating the three colonic regions. The transient viability of L. plantarum CECT 9435 within the child gut microbiota and its adhesion capacity to intestinal cells could facilitate the strain potential benefits as probiotic added to fortified supplementary foods destined to malnourished children.

Identifying bee species origins of Philippine honey using X-ray fluorescence elemental analysis coupled with machine learning - Angel T. Bautista VII; June Hope D. Aznar; Remjohn Aron H. Magtaas; Mary Margareth T. Bauyon; Andrei Joshua R. Yu; Joshua Kian G. Balaguer; Jervee M. Punzalan; Jessica B. Baroga-Barbecho; Cleofas R. Cervancia (Food Chemistry, 2025)

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

WITHDRAWN: Efficacy of diets with specific compositions to reduce the symptoms of immune-mediated diseases. Narrative review - Guerrero Aznar M Dolores; Villanueva Guerrero M Dolores; Hernández Cruz Blanca (PharmaNutrition, 2024)

Initial evaluation of USP apparatus 4 for measuring dissolution profile of man-made vitreous fibers - J.W. Hoffman; D.V. Okhrimenko; E. Chaudan; Q. Herault; N. Drnovsek; E. Pezennec; A. Aznar; N. Mascaraque; S. Haddouchi; M. Lecluse; A.A. Badissi; J. de Cruz; et al. (Toxicology Letters, 2023)

Raman-IR spectroscopic, and XRD analysis of selected samples from Fogo Island, Cabo Verde: Implications for ancient Martian volcanology - M. Aznar; A. Sanz-Arranz; S. Shkolyar; E.R. Sawyers; M. Konstantinidis; G. Lopez-Reyes; M. Veneranda; E.A. Lymer; J.R. Freemantle; M.G. Daly; E.A. Cloutis; F. Rull-Perez; et al. (Advances in Space Research, 2023)

Exploring the impact of lactic acid bacteria on the biocontrol of toxigenic Fusarium spp. and their main mycotoxins - Eva M. Mateo; Andrea Tarazona; Rosa Aznar; Fernando Mateo (International Journal of Food Microbiology, 2023)

Pseudidiomarina piscicola sp. nov., isolated from cultured European seabass, Dicenthrarchus labrax - M. Carmen Macián; Teresa Lucena; David R. Arahal; María A. Ruvira; Rosa Aznar; María J. Pujalte (Archives of Microbiology, 2021)
Strain CECT 9734 T , a Gram-negative, aerobic, chemoorganotrophic bacterium, motile by polar flagella, was isolated from cultured European seabass, Dicenthrarchus labrax, in Spain. It grows from 5 to 42 ºC, 6–9 pH and 1–12% total salinity. Major cellular fatty acids are C 15:0 iso, summed feature 9 (C 17:1 iso w9c /C 16:0 10-methyl) and C 17:0 iso. The genome size is 2.5 Mbp and G + C content is 49.5 mol%. Comparative analysis of the 16S rRNA gene sequence shows that the strain is a member of Pseudidiomarina , with highest similarities with Pseudidiomarina halophila (97.0%) and Pseudidiomarina salinarum (96.9%). Phylogenomic tree based on UBCG program shows P. halophila as its closest relative. ANI and in-silico DDH with other Pseudidiomarina spp. are lower than 87 and 20%, respectively, suggesting that strain CECT 9734 T represents a new species, for which we propose the name Pseudidiomarina piscicola sp. nov. and CECT 9734 T (= LUBLD50 7a T = LMG 31044 T ) as type strain.

Anthropogenic contaminants in freshwater from the northern Antarctic Peninsula region - Noelia Domínguez-Morueco; Luis Moreno-Merino; Daniel Molins-Delgado; M. Silvia Díaz-Cruz; Òscar Aznar-Alemany; Ethel Eljarrat; Marinella Farré; Jerónimo López-Martínez; Miren López de Alda; Adrián Silva; Juan José Durán Valsero; Yolanda Valcárcel (Ambio, 2021)

Epidemiology of Non-Tuberculous Mycobacteria isolated from clinical specimens in Madrid, Spain, from 2013 to 2017 - P López-Roa; E Aznar; J Cacho; R Cogollos-Agruña; D Domingo; MI García-Arata; R Millán; M Páez; E Perez-Cecilia; MJ Ruiz-Serrano; M Simón; M Tato; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Target of rapamycin signaling is tightly and differently regulated in the plant response under distinct abiotic stresses - Cintia M. Pereyra; Néstor R. Aznar; Marianela S. Rodriguez; Graciela L. Salerno; Giselle M. A. Martínez-Noël (Planta, 2020)

Tryptophan depletion affects compulsive behaviour in rats: strain dependent effects and associated neuromechanisms - A. Merchán; S. V. Navarro; A. B. Klein; S. Aznar; L. Campa; C. Suñol; M. Moreno; P. Flores (Psychopharmacology, 2017)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Fibroblast Migration in 3D is Controlled by Haptotaxis in a Non-muscle Myosin II-Dependent Manner - O. Moreno-Arotzena; C. Borau; N. Movilla; M. Vicente-Manzanares; J. M. García-Aznar (Annals of Biomedical Engineering, 2015)

Learning from Ecosystem-Based Management in Practice - Heather Leslie; Leila Sievanen; Tara Gancos Crawford; Rebecca Gruby; H. Cristina Villanueva-Aznar; Lisa M. Campbell (Coastal Management, 2015)

Challenges in the Modeling of Wound Healing Mechanisms in Soft Biological Tissues - C. Valero; E. Javierre; J. M. García-Aznar; A. Menzel; M. J. Gómez-Benito (Annals of Biomedical Engineering, 2015)

An improved taxonomic sampling is a necessary but not sufficient condition for resolving inter-families relationships in Caridean decapods - L. Aznar-Cormano; J. Brisset; T.-Y. Chan; L. Corbari; N. Puillandre; J. Utge; M. Zbinden; D. Zuccon; S. Samadi (Genetica, 2015)

Geological risk assessment of Amtoudi Agadir in southern Morocco: a key case for sustainable cultural heritage - P. Robles-Marín; F. Guerrera; M. Martín-Martín; G. Raffaelli; F. J. Alcalá; J. Tejera de León; T. E. Cherkaoui; L. Asebriy; I. E. El Amrani; S. Moliner-Aznar (Natural Hazards, 2015)

Computational Methodology to Determine Fluid Related Parameters of Non Regular Three-Dimensional Scaffolds - Víctor Andrés Acosta Santamaría; M. Malvè; A. Duizabo; A. Mena Tobar; G. Gallego Ferrer; J. M. García Aznar; M. Doblaré; I. Ochoa (Annals of Biomedical Engineering, 2013)

Three-Dimensional Simulation of Mandibular Distraction Osteogenesis: Mechanobiological Analysis - E. Reina-Romo; M. J. Gómez-Benito; A. Sampietro-Fuentes; J. Domínguez; J. M. García-Aznar (Annals of Biomedical Engineering, 2011)

Monitoring In Vivo Load Transmission Through an External Fixator - J. Grasa; M. J. Gómez-Benito; L. A. González-Torres; D. Asiaín; F. Quero; J. M. García-Aznar (Annals of Biomedical Engineering, 2010)

Analytical methods for the screening of potential volatile migrants from acrylic-base adhesives used in food-contact materials - C. Nerín; E. Canellas; M. Aznar; P. Silcock (Food Additives & Contaminants: Part A, 2009)

Lead Exclusion and Copper Translocation in Black Spruce Needles - J.-C. Aznar; M. Richer-Laflèche; C. Bégin; Y. Bégin (Water, Air, & Soil Pollution, 2009)

Does Increased Bone–Cement Interface Strength have Negative Consequences for Bulk Cement Integrity? A Finite Element Study - M.A. Pérez; J.M. García-Aznar; M. Doblaré (Annals of Biomedical Engineering, 2009)

Mining and Smelting Activities Produce Anomalies in Tree-growth Patterns (Murdochville, Québec) - J.-C. Aznar; M. Richer-Laflèche; C. Bégin; J. Marion (Water, Air, & Soil Pollution, 2007)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)